Pengembangan Kuis Menggunakan Wordwall Untuk Meningkatkan Motivasi Belajar Siswa Kelas IV SDN 01 Padang Laweh Pada Mata Pelajaran IPAS - Safitri, Auliya Nur; Ahmad Ilham Asmaryadi; Muhammad Subhan (Jurnal Tunas Pendidikan, 2025)
This research aims to develop a quiz using a wordwall to increase the learning motivation of class IV students at SDN 01 Padang Laweh in science subjects. This quiz aims to increase students' learning motivation. This type of research and development uses Research and Development (R&D). This quiz development model uses the ADDIE model (Analysis, design, development, implementation and evaluation). From the ADDIE model, a needs analysis, student characteristics analysis, material analysis, then expert validator test, practicality of students and educators and effectiveness seen from student motivation sheets are carried out. The results of developing a quiz using a wordwall to increase the motivation of class IV students at SDN 01 Padang Laweh in the science and sciences subject were declared very valid. Based on the results obtained from the validator, an average score of 86.27% was obtained in the very valid category. Practicality results with an average of 92.85% are very practical. For effectiveness, by filling out the motivation questionnaire, an average score of 85.47% was categorized as very effective. It can be concluded that the quiz created is valid, practical and effective for educators to use in learning.